Penerapam Permainan Sambung Kata untuk Meningkatkan Keterampilan Menulis Puisi Siswa Kelas V SD Inpres 189 Kanite di Kabupaten Takalar - Ramlah Ramlah; Muhammad Akhir; Abdan Syakur (Departement of Mathematics Education, 2024)
This research is a type of Classroom Action Research (PTK) which consists of 4 stages, namely planning, implementation, observation and reflection. This research was carried out at SD Inpres 189 Kanite, South Galesong District, Takalar Regency with the research subjects being 20 students in class V of SD Inpres 189 Kanite. The instruments of this research are an observation sheet and a poetry writing skills test. Observation, test and documentation data collection techniques. The results of the research regarding the application of the word connect game method to improve the poetry skills of fifth grade students at SD Inpres 189 Kanite are: (1) The application of the word connect game can increase students' vocabulary and word choice so that it can improve students' poetry writing skills. (2) And the word connection game can improve students' poetry writing skills as seen from the percentage of students who completed it in cycle I was 25%, and in cycle II the percentage of students who completed it was 85%.